East Anglian English - Trudgill, Peter 1943- (Dialects of English, 2021)
This book is the first full-scale scientific study of East Anglian English. The author is a native East Anglian sociolinguist and dialectologist who has devoted decades to the study of the speechways of Norfolk, Suffolk, Cambridgeshire and Essex. He examines their relationships to other varieties of English in Britain, as well as their contributions to the formation of American English and Southern Hemisphere Englishes